Polyamidoamine dendrimer and dextran conjugates: Preparation, characterization, and in vitro and in vivo evaluation - Shrivastava P.K.; Singh R.; Shrivastava S.K. (My University, 2025)
Amide and ester conjugates of aceclofenac with polyamidoamine (PAMAM-G0) dendrimer zero generation and dextran (40 kDa) polymeric carrier, respectively, are presented. The prepared conjugates were characterized by UV, TLC, HPLC, IR, and 1H NMR spectroscopy. The average degrees of substitution of amide and ester conjugates were determined and found to be (12.5 ± 0.24) % and (7.5 ± 0.25) %, respectively. The in vitro hydrolysis studies showed that dextran ester conjugate hydrolyzed faster in a phosphate buffer solution of pH 9.0 as compared to PAMAM dendrimer G0 amide conjugate, and followed the first order kinetics. No amount of the drug was regenerated at pH 1.2 in simulated gastric fluid. The dextran conjugate showed short half-life as compared to the PAMAM dendrimer conjugate. Anti-inflammatory and analgesic activities of the dendrimer conjugate were found to be similar to those of the standard drug. Results of chronic ulceroginic activity showed deep ulceration and high ulcer index for aceclofenac, whereas lower ulcer index was found for the PAMAM dendrimer and dextran (40 kDa) conjugates. Experimental data suggest that PAMAM dendrimer and dextran (40 kDa) can be used as carriers for the sustained delivery of aceclofenac along with a remarkable reduction in gastrointestinal toxicity. © 2010 Institute of Chemistry, Slovak Academy of Sciences.